Myofibroblastoma of the Breast: A Rare Cause of Breast Lump in a Postmenopausal Woman - Yasmeen Khatib; Vinita Pandey; Archana L Khade; Rahul Pandey (Wolters Kluwer Medknow Publications, 2018)
A breast mass in a postmenopausal age woman is treated with a high index of clinical suspicion for malignancy. Myofibroblastoma (MFB) of the breast is a very rare benign stromal tumor, predominantly occurring in menopausal women and older men. Owing to its rarity, nonspecific radiology, cytomorphology, and many variants, it can be confused with other malignant and benign breast lesions and hence can be a source of diagnostic pitfall. We present a case of an MFB of the breast in a 55-year-old female, which was detected on a routine screening mammography. Fine-needle aspiration cytology was inconclusive. Final diagnosis was made by histopathology and immunohistochemistry examination. We report this case as the likelihood of encountering MFB has increased in recent years due to routine mammographic screening, and this lesion should be kept in the differential diagnosis of spindle-cell lesions of the breast.